The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18639/rabm.2019.858317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Air Condition Use and Its Health Effects

Abstract: The use of air conditioners (ACs) in homes has become a necessity in urban cities such as Lagos State. The rapid growth in the use of AC has been attributed majorly to protection from high thermal exposures. However, there have been controversies regarding physiological discomforts attributed to AC use. This study therefore seeks to elucidate the associations between AC use and some selected physical ailments using random samples from Lagos State. A structured questionnaire was administered to 200 randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to Sarafraz, Sadani, and Teimouri (2018), household particulate matter has indoor and outdoor sources [11]. Consequently, indoor air quality is influenced by outdoor air quality [12], and indoor sources, such as heating and cooling systems, cooking facilities that use fossil fuels (oil, gas, kerosene, coal, and wood), smoke, building materials, furniture, carpets, cleaning products, maintenance products, and personal hygiene [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…According to Sarafraz, Sadani, and Teimouri (2018), household particulate matter has indoor and outdoor sources [11]. Consequently, indoor air quality is influenced by outdoor air quality [12], and indoor sources, such as heating and cooling systems, cooking facilities that use fossil fuels (oil, gas, kerosene, coal, and wood), smoke, building materials, furniture, carpets, cleaning products, maintenance products, and personal hygiene [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates are that as much as 5% of patients who visit hospitals for treatment develop nosocomial (hospital-acquired) infections while in a hospital or other health care facility (Kishor and Lokesh 2018). Further, numerous studies have also shown that occupants of office buildings with HVAC systems consistently report more symptoms related to mucous membrane irritation, breathing difficulties, irritated skin and constitutional/neurological symptoms such as headache and fatigue in their buildings than do occupants of buildings with natural ventilation (Eleyowo and Amusa 2019;Mendell 2004;Prussin and Marr 2015;Yamamoto et al 2015). Such symptoms could be linked to the production of allergens, endotoxins and bacterial volatile organic compounds (VOCs) by bacterial contaminants in HVAC systems.…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration of indoor air quality has been attributed mostly to the presence of aeroallergens and bio-aerosols, including bacteria, fungi and viruses (Brągoszewska et al 2018;Fekadu and Getachewu 2015;Macher et al 1991). The installation of heating, ventilation and air conditioning (HVAC) systems in offices and other buildings is therefore designed to enhance comfort by maintaining ideal levels of humidity (typically between 40 and 60%) and temperature (Eleyowo and Amusa 2019;Ito et al 2018), as well as improving the quality of indoor air by filtering out bio-aerosols, dust, allergens and reducing odours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation